Upaya Pencegahan Stunting Melalui Pemberian Makanan Tambahan dan Penerapan Pola Hidup Bersih Sehat di PAUD Tunasmulya Desa Pabean Kecamatan Dringu Kabupaten Probolinggo - Flavia Aurelia Hidajat (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2019)
Stunting or short is a problem that grows in children under five who are malnourished more than the first 1,000 days of life. Unbalanced nutrient intake is one factor that is recognized directly for stunting. By meeting the nutritional needs of children and habituating healthy lifestyles, is expected to prevent stunting for children. Tunas Mulya and the promotion of a healthy lifestyle for parents. From the program that we have implemented in Paud Tunas Mulya, we can get the results from the awareness of teachers and parents that they will need nutritious food assistance and a healthy lifestyle for children. Keywords: Stunting, Provision of Supplementary Food, PHBS, and Paud Tunas Mulya Customs Village